Effects of pre-cooling and cooling breaks on thermoregulatory, physiological and match running responses during football in moderate and hot temperatures - Schwarz, E.; Oliveira, C. B.; Muñoz, M. D.; Alanis, A.; Alanis, M.; Lara, A.; Freeze, A.; Costa, J. A.; Meyer, T.; Duffield, R. (Sports Medicine, 2026)
Purpose: This study investigated the effects of pre-cooling and cooling breaks on thermoregulatory, hydration and running responses in football (soccer) players in moderate and hot temperatures. Methods: Forty male youth footballers participated in at least two of four matches, during which core body temperature (Tcore), heart rate (HR), match running, hydration and perceptual responses were measured. Cooling breaks (CBs), consisting of ice-cold towels and drinks, were compared to drinking breaks (DBs), consisting of passive rest and a temperate drink, applied at the same timeframes. Both were used as pre-cooling for 10 min before the warm-up, before the pre-match, during half-time and during additional 3-min cooling breaks at the 25th minute of each half. Initially, 20 players performed two crossover matches in 25 °C wet-bulb globe temperature (WBGT) receiving cooling (CB25) and drinking (DB25). A second group of 20 players played a regular match in 25 °C WBGT with no breaks (NB25) and then a match in 33 °C WBGT during which they received either cooling (CB33) or drinking breaks (DB33). Results: In CB25, players felt cooler (p < 0.001) and less fatigued (p < 0.045) than in DB25, without differences in match running (p > 0.20), HRmean (p > 0.35) or Tcore (p > 0.09). Players in CB25 sweated less (p = 0.005) and drank less (p = 0.002), resulting in no significant difference in body mass loss compared to DB25. In CB33, players had lower HRmean (p = 0.007), similar total distance (p = 0.21), lower peak Tcore (p < 0.001) and lower body mass loss (p = 0.007) compared to NB25. In DB33, players reduced moderate (12-18 km/h; p = 0.007) and high-speed running distance (18-24 km/h; p = 0.002) but had similar peak Tcore (p = 0.71) and body mass loss (p = 0.95) to that in NB25. Conclusions: In general, high Tcore values and body mass losses were observed even when playing in moderate heat. Both drinking and cooling breaks attenuated the continuous Tcore rise, but using cooling also improved player perceptions in moderate temperatures. In hotter temperatures, cooling breaks further lowered Tcore and body mass loss compared to using only drinking breaks.